El rol de los medios de comunicación radial local y su incidencia en la difusión del turismo de la comunidad shuar “Martín Ujukam”, cantón Zamora, período abril-septiembre de 2013. Propuesta alternativa - Sarango Uchuari, Mirian Alba (2015)
This research report refers to the analysis and description of the role of local radio communication media as an essential tool for the dissemination and strengthening of tourist attractions in the Shuar community, "Martin Ujukam". The research was conducted with the choice of theme: "THE ROLE OF LOCAL MEDIA RADIO COMMUNICATION AND ITS IMPACT ON THE RELEASE OF TOURISM OF COMMUNITY SHUAR" MARTIN UJUKAM "CANTON ZAMORA, April - September 2013. ALTERNATIVE PROPOSAL ". Once the process structured data collection, direct observation and then a survey of population Zamora, obtaining valuable results allowed validation and go beyond the investigative purpose was conducted. Firstly, the population was investigated in general, then to the various authorities of the Canton Zamora and finally the people of the Shuar Community Martin Ujukam, where he managed to talk to them and directly perceive the reality in which they live; forgotten as to the means of radio communication and tourism is concerned. The books of the Shuar culture also encouraged and further enriched the knowledge related to worldview and modus vivendi of the Shuar world. One of the results was the lack of tourist diffusion that exists on the Shuar community Martin Ujukam; ie no interest from the media and thus do not meet their main functions: to inform, educate and entertain, just are focused on the business side. In other words, pending further rating and your pocket, a social problem that ignores the real role of radio communication.Another important result that was found is that very little attention is offered to the different cultures found in our environment, since the support of the different authorities is minimal.For this reason, this research theme is intended to encourage and strengthen the tourism diffusion of surrounding communities of Canton Zamora, specifically of the Shuar Community Martin Ujukam.